Analysis of The Use of Mobile Phones in Studying Biology by Students in The Village of Suralaga, East Lombok Regency - Risa Umami; Nining Purwati; Lia Rahmatul Maulani (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2022)
This study aims to analyze the use of mobile phones in learning biology among students in Suralaga village, Suralaga sub-district, East Lombok district. The focus of the research includes: (1) the effect or impact of the use of cell phones, (2) the intensity and time of using cell phones, and (3) the application of the use of cell phones in learning biology. This study uses a descriptive qualitative approach. The population in this study was 120 students, and the sample of respondents in this study was 36 students, consisting of three levels of education, namely elementary, junior high, and high school. The results showed that mobile phones were very influential in making it easier for students to find new learning methods. The impact of using cell phones includes: helping students to work on assignments and adding insight into science, social interaction, and student environment becoming ignorant of each other, cellphone addiction causes students to concentrate less on learning, forget time, and feel annoyed if someone interrupts him playing his cellphone. Students are said to be cellphone addicts because they use cell phones for a long duration, the intensity of using cellphones in a day is up to ≥ 6 hours day and their use is more often used in the afternoons – evenings, the application form of using cellphones in learning biology is looking for Latin terms, looking for videos biology learning and so on